Segmented simultaneous multi‐slice diffusion‐weighted imaging with navigated 3D rigid motion correction. Issue 3 (6th May 2021) - Riedel (né Steinhoff), Malte; Setsompop, Kawin; Mertins, Alfred; Börnert, Peter
Abstract : Purpose: To improve the robustness of diffusion‐weighted imaging (DWI) data acquired with segmented simultaneous multi‐slice (SMS) echo‐planar imaging (EPI) against in‐plane and through‐plane rigid motion. Theory and Methods: The proposed algorithm incorporates a 3D rigid motion correction and wavelet denoising into the image reconstruction of segmented SMS‐EPI diffusion data. Low‐resolution navigators are used to estimate shot‐specific diffusion phase corruptions and 3D rigid motion parameters through SMS‐to‐volume registration. The shot‐wise rigid motion and phase parameters are integrated into a SENSE‐based full‐volume reconstruction for each diffusion direction. The algorithm is compared to a navigated SMS reconstruction without gross motion correction in simulations and in vivo studies with four‐fold interleaved 3‐SMS diffusion tensor acquisitions. Results: Simulations demonstrate high fidelity was achieved in the SMS‐to‐volume registration, with submillimeter registration errors and improved image reconstruction quality. In vivo experiments validate successful artifact reduction in 3D motion‐compromised in vivo scans with a temporal motion resolution of approximately 0.3 s. Conclusion: This work demonstrates the feasibility of retrospective 3D rigid motion correction from shot navigators for segmented SMS DWI.